Conversion therapy for advanced hepatocellular carcinoma with vascular invasion: a comprehensive review - Zhang, Zunyi; Zhang, Erlei (Frontiers in Immunology, 2023)
Hepatocellular carcinoma (HCC) is the most common type of liver cancer with a high mortality rate worldwide. The percentage of HCC patients with vascular invasion at the time of initial HCC diagnosis is 10%-40%. According to most guidelines, HCC with vascular invasion is classified as advanced stage and resection is only suggested for a minority of such patients. Recently advances in systemic and locoregional treatments for such patients have resulted in amazing response rates. So ‘Conversion therapy’ strategy including systemic and locoregional treatments is proposed to selected patients from initially unresectable state to eventually perform R0 resection. Recently, lots of studies have proven that conversion therapy followed by subsequent surgery is achievable in well selected advanced HCC and can provide a prolong long-term outcomes. Based on the published research, this review has summarized the clinical experience and evidence of conversion treatment in HCC patients with vascular invasion.